Comparative Analysis of the Effectiveness of Beet Juice (Beta Vulgaris L) with Guava Juice (Psidium Guajava) in Increasing Hemoglobin Levels of Postpartum Mothers in the Health Service Area of Darul Imarah, Aceh Besar District, Indonesia - Nurhasanah, Cut; Gustiana,; Novemi,; Yushida, (International Journal of Psychosocial Rehabilitation, 2020)
Anemia is thought to occur frequently in puerperal women. The puerperal period of the mother experiences physiological bleeding after the release of the placenta. This condition will cause a decrease in maternal blood especially hemoglobin resulting in the mother can experience anemia. While postpartum mothers have lost blood and must provide breast milk for babies with good nutritional balance. Prevention and treatment of anemia can be done by consuming herbal foods, such as Beta Vulgaris L (beetroot) and Psidium guajava (guava). Objectives: Analyzing the Comparison of the Effectiveness of Beet Juice (Beta Vulgaris L) with Guava Juice (Psidium Guajava) in Increasing Hemoglobin Levels of Postpartum Mothers in the Work Area of Darul Imarah Health Center, Aceh Besar District, Indonesia. Methodology: To find out the difference between the effectiveness of beet juice and Guava juice to increase hemoglobin levels of postpartum mothers, quasi-experiments with randomized controlled trials were used with pretest and post-test designs. The study was conducted on postpartum mothers at the Darul Imarah Health Center, Aceh Besar, from August to December 2019. While this population is postpartum mothers who have anemia. While the sample was taken by purposive sampling technique for 45 people with inclusion and exclusion criteria. Inclusion criteria are postpartum mothers who have HB 6-9 gr/dl, are willing to be sampled, have no complications of the disease, have healthy babies. Data analysis using univariable, and bivariable using One Way Anova test. Results: Normality test results were normally distributed in the treatment group and the control group showed differences in hemoglobin levels before and after the treatment of beet and Fe juice with a p-value of 0,000